Antimicrobial and Antiviral Compounds of Phlomis viscosa Poiret - Ludmila Yarmolinsky; Faina Nakonechny; Arie Budovsky; Haim Zeigerman; Boris Khalfin; Eyal Sharon; Leonid Yarmolinsky; Shimon Ben-Shabat; Marina Nisnevitch (Biomedicines, 2023)
Phlomis viscosa Poiret (an evergreen shrub) represents a valuable source of medicinal compounds. In this study, we discovered compounds with antimicrobial and antiviral properties. The aim of this study was to identify compounds of P. viscosa and estimate the antimicrobial and antiviral activity of its phytochemicals. The volatile compounds were identified using gas chromatography/mass spectrometry (GC/MS) analysis. For the identification of nonvolatile components of the extracts, high-performance liquid chromatography (HPLC), liquid chromatography–electrospray ionization-mass spectrometry (LC-ESI-MS) and matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry (MALDI-TOF-MS) were applied. Quercetin 3-O-rutinoside and hesperidin caused a significant decrease in the bacterial concentration of Agrobacterium tumefaciens, Xylella fastidiosa and Pseudomonas syringae (p < 0.001). The growth of drug-resistant microorganisms (Escherichia coli, Klebsiella pneumoniae, Acinetobacter baumannii, Serratia marcescens and Salmonella enteritidis) was inhibited by quercetin 3-O-rutinoside, quercetin 3-O-arabinoside and hesperidin. In addition, these compounds demonstrated antiquorum-sensing properties. Diosmin, hesperidin and quercetin 3-O-arabinoside significantly inhibited varicella zoster virus (VZV) (p < 0.001). Quercetin 3-O-rutinoside and quercetin 3-O-arabinoside were effective against herpes simplex virus 1 (HSV-1), including mutant strains.